The Levels and Distribution of Polycyclic Aromatic Hydrocarbons (PAH) Contamination in Bottom Sediments in Manila Bay - Santiago, Evangeline (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The concentration levels of 18 PAH compounds extracted from 19 bottom sediments from the Limay Coast and 16 bottom sediments from the coast along Metro Manila and Cavitc Province of Manila Bay were determined by Gas Chromatography/Mass Spectrometry. The PAH contamination, the levels of other non-PAH petroleum hydrocarbon compounds. and total organic content in the sediments were assessed in relation to the location and depth of the sampling sites. The PAH concentrations and the levels of other petroleum hydrocarbons in the sediments showed that the spatial distribution of PAH and other hydrocarbon contamination in Manila Bay is largely dependent on the proximity of the sediment deposition site to known point sources of pollution. On the western side, the highest levels of PAH contamination normalized to % TOC (1.29 X 10 4 at Ll2, 1.28 x 10 4 at Ll6, 0.55 at Ll3, and 0.54 at Ll5) were obtained from sediments collected at deposition sites near the outfall of the Petron Oil Refinery. On the eastern side. sediments located at the effiuent zones of the Paranaque and Malabon Rivers showed excessively higher levels of PAH normalized to % TOC (3.32 x 10 4 and 2.87 x 10 4 : respectively) compared to those obtained from other sites in the area. The PAH contamination in the sediments from Manila Bay is dominated by alkylated naphthalenes and phenanthrenes which are associated with petrogenic sources. This indicates that the surface sediments in Manila Bay are ex-posed to chronic contamination of petroleum hydrocarbons introduced mainly by direct spillage on the western side and by urban run-off on the eastern side.